Kidnapped - Jones,Rob Lloyd (London: Usborne, 2012)
old into slavery by his greedy uncle, David Balfour's only hope of escape is by siding with the outlaw Alan Breck. Follow his daring adventure, in this classic tale of kidnap, shipwreck, and survival in the wild Scottish Highlands
Keywords: Adventure stories